Epidemiological profile of cervical cancer in the State of Maranhão, Brazil (Research, Society and Development, 2022)
Aim: to evaluate the epidemiological profile of cytopathological examinations of the cervix, registered in SISCAN, carried out from 2016 to 2022, in the State of Maranhão, Brazil. Method: epidemiological study of a descriptive nature and with a quantitative and retrospective approach. The following variables were analyzed: year of results, age group, previous cytology, reason for the exam, sample suitability and cellular changes in the exam. Data were categorized and tabulated using Microsoft Office Excel 2016 software, arranged in figures and tables. Results: 1,120,465 exams were recorded, the largest number belonging to the age group from 30 to 34 years. Screening was the main motivation for performing the exam. As for suitability, a higher frequency of smears classified as satisfactory was observed. Inflammation was the main finding among benign cellular changes. Possibly non-neoplastic atypia of undetermined significance (ASC-US) and low-grade intraepithelial lesions (LSIL) represent the highest percentage found in squamous cell abnormalities. Invasive adenocarcinoma corresponded to the main finding of abnormalities in glandular cells. Final Considerations: through this study, it is expected that there will be implementation of health education actions and increasingly efficient preventive approaches that help to reduce the number of positive cases for Cervical Cancer (CCU), since the lack of adequate information about the CCU is a factor that makes it difficult to perform the exams periodically.